Goal orientations predict academic performance beyond intelligence and personality - Steinmayr, Ricarda; Bipp, Tanja; Spinath, Birgit (Learning and individual differences, 2011)
Goal orientations are thought to be an important predictor of scholastic achievement. The present paper investigated the joint influence of goal orientations, intelligence, and personality on school performance in a sample of N=520 11th and 12th graders (303 female; mean age M=16.94years). Intelligence, the Big Five factors of personality (Neuroticism, Extraversion, Openness to Experience, Agreeableness, and Conscientiousness) as well as goal orientations (learning, performance-approach, -avoidance, and work-avoidance goals) were assessed. When school performance was regressed on all variables simultaneously, intelligence, Openness to Experience, Conscientious, and learning goals predicted school performance. Learning goals additionally partially mediated the association of Openness to Experience and Conscientious, respectively, with GPA. Results are discussed with regard to the importance of goal orientations in academic settings.